If it's not what You are looking for type in the equation solver your own equation and let us solve it.
Simplifying solve(x + -1)(2x + -5) = 9 Reorder the terms: elosv(-1 + x)(2x + -5) = 9 Reorder the terms: elosv(-1 + x)(-5 + 2x) = 9 Multiply (-1 + x) * (-5 + 2x) elosv(-1(-5 + 2x) + x(-5 + 2x)) = 9 elosv((-5 * -1 + 2x * -1) + x(-5 + 2x)) = 9 elosv((5 + -2x) + x(-5 + 2x)) = 9 elosv(5 + -2x + (-5 * x + 2x * x)) = 9 elosv(5 + -2x + (-5x + 2x2)) = 9 Combine like terms: -2x + -5x = -7x elosv(5 + -7x + 2x2) = 9 (5 * elosv + -7x * elosv + 2x2 * elosv) = 9 (5elosv + -7elosvx + 2elosvx2) = 9 Solving 5elosv + -7elosvx + 2elosvx2 = 9 Solving for variable 'e'. Move all terms containing e to the left, all other terms to the right. Reorder the terms: -9 + 5elosv + -7elosvx + 2elosvx2 = 9 + -9 Combine like terms: 9 + -9 = 0 -9 + 5elosv + -7elosvx + 2elosvx2 = 0 The solution to this equation could not be determined.
| 16(3x-2)=4(12x+4) | | 15x-20+35x=180 | | 10x=-15 | | 10=-15 | | 10-(2n-5)=2-3n | | Y=X^2+7x-8 | | 6y-7=7y-6 | | 3x^2+17x+24=0 | | x+25+55=180 | | x=40y | | 10v^2-21=0 | | x=-3.5+0.5y | | -3x^2+343=0 | | 5p-4(1-3p)=4p-(p+1) | | x^2+8x+7=-8 | | 3xy^2*2x^0= | | x^3+(4*x^2)+4*x=0 | | 2x(4-7x)-x(4x+5)=4x+81 | | 6b+7=-5 | | 9x^2-28x-28=0 | | 25z^2-20z+4=0 | | 115=x*1.03 | | 115=x*.03 | | -2(x-4)=5-(x+2) | | 4=-4x | | 4a^2-a-3=0 | | 4=-4 | | 2(5z-1)-2(z+3)=3(z+1) | | 47=8-12x | | 2s^2+5s+3=0 | | 38=14+9a | | 2[3x-1]+2=10 |